2021
DOI: 10.3390/ijerph18084104
|View full text |Cite
|
Sign up to set email alerts
|

Driving Behavior That Limits Concentration: A Nationwide Survey in Greece

Abstract: Human behavior is implicated in most road accidents. The current study examined drivers’ behavior that interferes with decision making and reaction time to an incidence. Adults (≥17 years-old) participated in a questionnaire-based survey for driver’s behavior. Dataset was weighed according to sex, age and education based on the 2011 census. Differences between groups were assessed with Chi-squared tests while logistic regression models were used to identify drivers’ characteristics for specific behaviors. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Tobacco use might decrease the subjective intoxicating and sedating effects of alcohol, leading to heavier drinking episodes [42]. Finally, tobacco use while driving has been associated with road accidents [46,47]. Independent of the aim of the study, it is interesting to highlight that the prevalence of tobacco use disorder in our samples (cases and the comparison group) was almost three times that observed in the overall Italian population [48].…”
Section: Discussionmentioning
confidence: 79%
“…Tobacco use might decrease the subjective intoxicating and sedating effects of alcohol, leading to heavier drinking episodes [42]. Finally, tobacco use while driving has been associated with road accidents [46,47]. Independent of the aim of the study, it is interesting to highlight that the prevalence of tobacco use disorder in our samples (cases and the comparison group) was almost three times that observed in the overall Italian population [48].…”
Section: Discussionmentioning
confidence: 79%
“…The following are some of the risk factors identified by the WHO related to human errors: (1) speeding–every 1% increase in the mean speed increases fatal crash risk probability by 4%, (2) seatbelt usage–usage will reduce fatality by 45–50% for front-seat occupants, (3) driving under the influence of psychotropic substances–can increase risk by about five times, and (4) distracted driving–usage of mobile phones can increase the risk of an accident by 4 folds. Many studies have been published supporting the claim by the WHO, indicating that risky driving behaviors are one of the leading causes of road accidents [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 91%
“…Additionally, tobacco use may reduce the subjective effects of alcohol, potentially leading to increased alcohol consumption [ 38 ]. In this regard, other scholars [ 39 , 40 ] have also linked smoking while driving to an increased risk of road crashes. This behavior, although not perceived as distracting by most drivers, is recognized as leading to distractions and, thus, as a risk factor for traffic collisions [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, other scholars [ 39 , 40 ] have also linked smoking while driving to an increased risk of road crashes. This behavior, although not perceived as distracting by most drivers, is recognized as leading to distractions and, thus, as a risk factor for traffic collisions [ 40 ]. Previous studies by the authors [ 6 , 33 ] have already shown a significant correlation between smoking and DUI recidivism or excessive alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%